Impact of Respiratory Viral Infections on Alpha Hemolytic Streptococci and Otopathogens in the Nasopharynx of Young Children - Friedel, Victoria (2013)
BACKGROUND: We studied nasopharyngeal (NP) colonization in a cohort of children to determine the impact of viral upper respiratory infections (URI) on non-pneumococcal alpha hemolytic streptococci (AHS) and otopathogen colonization in association with acute otitis media (AOM). METHODS: NP samples were collected routinely when children were aged 6, 9, 12, 15, 18, 24, and 30 months and during episodes of AOM. NP samples were prospectively obtained from 248 children during a 5-year time span; 1,018 during routine visits, 161 at the time of AOM and 59 at follow-up visits 3 weeks after AOM. RESULTS: The overall NP colonization rate of AHS was 50.8% during a non-AOM visit but declined to 38.3% during a viral URI with concurrent AOM (p=0.0006). Of 56 AOM visits with paired follow-ups, 6 (10.7%) had AHS in the NP at the time of viral URI and concurrent AOM whereas 29 (51.8%) had AHS at the follow-up (p<0.001). Lower NP colonization rates with AHS were associated with significant increases in Streptococcus pneumoniae carriage during non-AOM visits (p<0.001) and during viral URI and concurrent AOM visits (p=0.003). AHS NP colonization rates were not different when children had a viral URI without AOM versus when they were URI negative, but NP colonization with non-typeable Haemophilus influenzae rates increased (p<0.001) and Moraxella catarrhalis decreased (p<0.001) during viral URI. CONCLUSION: Respiratory viral infections alter NP carriage rates of commensal AHS and otopathogens, including prior to AOM.